2006
DOI: 10.31421/ijhs/12/1/629
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of chamomile (Matricaria recutita L.) populations from different origin

Abstract: In our research project under cultivation we examined 4 cultivars ('Soroksári 40', 'Lutea , 'Goral', 'Bona') and 28 wild populations of chamomile assuring all of them the same environmental conditions. Plant height, flower-diameter, essential-oil content, and the main terpenoid and flavonoid composition were analysed. The aim of our study was to establish the genetic background of breeding a new cultivar as well as encircle those natural habitats that give chamomile drug with the best quality. In the cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Continued tably (E)-β-farnesene, oxygenated sesquiterpenes prevailed in samples B and F (α-bisabolol oxides A and B, α-bisabolone oxide A) as well as sample E (main compound α-bisabolol). The latter had also notably high concentrations of azulenes (21.8 %) and spiroethers (16.9 %), not only compared to the other samples ( < 10 %) but also other samples from Hungary [15]. As both α-bisabolol [8,16] and chamazulene [17][18][19] proved to possess anti-inflammatory and highly antioxidant properties [14,17,20], this combination is highly preferable for pharmaceutical and cosmetic use.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Continued tably (E)-β-farnesene, oxygenated sesquiterpenes prevailed in samples B and F (α-bisabolol oxides A and B, α-bisabolone oxide A) as well as sample E (main compound α-bisabolol). The latter had also notably high concentrations of azulenes (21.8 %) and spiroethers (16.9 %), not only compared to the other samples ( < 10 %) but also other samples from Hungary [15]. As both α-bisabolol [8,16] and chamazulene [17][18][19] proved to possess anti-inflammatory and highly antioxidant properties [14,17,20], this combination is highly preferable for pharmaceutical and cosmetic use.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, a variant low in matricin (prochamazulene) was mentioned. This classification has been used by many authors [13,15,26,27], however, Type A and B have been interchanged. Later, Horn et al [28] could identify four chemotypes as follows: Type I dominated by α-bisabolol and matricin, Type IIa by α-bisabolol oxide A and matricin, Type IIb by α-bisabolol oxide B and matricin, and Type III high in α-bisabolone oxide but devoid of α-bisabolol and matricin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is a fast and practical method, aiming to the determination of all apigenin derivatives, it causes degradation of many other components, thus altering considerably the phenolic profile of the extracts [22]. A literature survey showed that most of the quality assessment studies on chamomile focus mainly on the essential oils [23][24][25][26], whereas the majority of HPLC analytical methods limit to the determination of apigenin and apigenin-7-O-glucoside in extracts or decoctions, without measuring the flavonoid/phenol content in the herbal drug, which is nevertheless the raw material. The only exception is the report on the qualitative and quantitative profile of phenolic constituents of several commercial chamomile samples by Avula et al [27].…”
Section: Introductionmentioning
confidence: 99%
“…Polyploidy has led to an increase in secondary metabolites in medicinal plants in two ways: first, by the increase of biomass in chromosome doubled plants, and second, by the increase in number of gene copies related to the pathways of the secondary metabolites. Examples of higher levels of secondary metabolites after chromosome doubling are the increase of alkaloids in Datura stramonium (Berkov and Philipov, 2002) and Atropa belladonna (Huang et al, 2010), essential oils and chamazoline in Matricaria chamomile (Gosztola et al, 2006), terpenoids and flavonoids in Salvia miltiorrhiza (Gao et al, 1996) and morphine content in Papaver somniferum (Mishra et al, 2010).…”
Section: Introductionmentioning
confidence: 99%